The role of cell surface heparan sulfate in enterovirus A71 infections and the development of antiviral agents targeting viral attachment and RNA translation initiation / Tan Chee Wah - Tan, Chee Wah (2014)
Enterovirus A71 (EV-A71) is the main causative agent of hand, foot and mouth disease (HFMD). Recent EV-A71 outbreaks in Asia-Pacific were not limited to mild HFMD, but were associated with neurological complications including aseptic meningitis, brainstem encephalitis and deaths. The absence of licensed therapeutics for clinical use has intensified research into anti-EV-A71 development. Since virus-host receptor interaction is the first essential event during virus infection, inhibitors that block this event could act as potential therapeutics. EV-A71 VP1 capsid protein is involved in viral-host receptor interactions and carries multiple receptor binding sites. Screening of 95 overlapping peptides covering the entire EV-A71 VP1 capsid protein was hypothesized to identify potential viral attachment inhibitors, as well as unknown receptors. Out of 95 overlapping peptides, a peptide designated as SP40 peptide significantly inhibited EV-A71-induced cytopathic effect, plaque formation, RNA synthesis and viral protein synthesis. Mechanism of action analysis revealed that SP40 peptide is not virucidal, but blocked EV-A71 attachment to the cell surface. Alanine scanning analysis showed that positively charged amino acids were critical for the antiviral activities. Sequence analysis revealed that SP40 peptide carried a heparan sulfate-specific binding domain (-RRKV-), which led to the hypothesis that EV-A71 could use cell surface heparan sulfate as an attachment receptor. Highly sulfated heparin, dextran sulfate and suramin significantly inhibited EV-A71 infections in a dosedependent manner. Interference with heparan sulfate biosynthesis either by sodium chlorate treatment or through transient knockdown of N-deacetylase/N-sulfotransferase- 1 and exostosin-1 expression reduced EV-A71 infection. Enzymatic removal of cell surface heparan sulfate by heparinase I/II/III inhibited EV-A71 infection. Biochemistry analysis revealed that EV-A71 interacts with heparan sulfate through electrostatic interactions. These findings support the hypothesis and confirmed that EV-A71 uses iv cell surface heparan sulfate as an attachment receptor. Other than the attachment inhibitor, this study also tested DNA-like antisense-mediated morpholino oligomers as anti-EV-A71 agents. Two octaguanidinium-conjugated morpholino oligomers (vivo- MOs) targeting EV-A71 internal ribosome entry site (IRES) significantly inhibited EVA71 infections at multiple time points, in a dose-dependent manner. EV-A71 resistance to vivo-MO-1 arose after 8 blind passages in the presence of increased concentrations of vivo-MO-1, but not vivo-MO-2. A single nucleotide mutation at the extreme 3’ end (T to C substitution at position 533) was sufficient to confer vivo-MO-1 resistance. In mismatch tolerance analysis, results demonstrated that the positions and the number of mismatches affect vivo-MO-1 efficacy. A single mismatch at the center of the targeted region was more tolerable compared to a mismatch at the end of the targeted region. In conclusion, this study has identified an antiviral peptide that potentially blocks viral attachment to heparan sulfate, and led to the discovery of a novel EV-A71 attachment receptor. This study also identified two antisense-mediated vivo-MOs targeted sites for antiviral intervention. This study suggests that blocking of viral attachment and viral RNA translation are good strategies for antiviral intervention.